Creating a provincial post COVID‐19 interdisciplinary clinical care network as a learning health system during the pandemic: Integrating clinical care and research - Adeera Levin; Michelle Malbeuf; Alison M Hoens; Christopher Carlsten; Christopher J Ryerson; Alessandro Cau; Stirling Bryan; Jaclyn Robinson; Tamsin Tarling; Joanne Shum; Danielle C Lavallee (Wiley, 2023)
Abstract Introduction Coronavirus Disease‐2019 (COVID‐19) affects multiple organ systems in the acute phase and also has long‐term sequelae. Research on the long‐term impacts of COVID‐19 is limited. The Post COVID‐19 Interdisciplinary Clinical Care Network (PC‐ICCN), conceived in July 2020, is a provincially funded resource that is modelled as a Learning Health System (LHS), focused on those people with persistent symptoms post COVID‐19 infection. Methods The PC‐ICCN emerged through collaboration among over 60 clinical specialists, researchers, patients, and health administrators. At the core of the network are the post COVID‐19 Recovery Clinics (PCRCs), which provide direct patient care that includes standardized testing and education at regular follow‐up intervals for a minimum of 12 months post enrolment. The PC‐ICCN patient registry captures data on all COVID‐19 patients with confirmed infection, by laboratory testing or epi‐linkage, who have been referred to one of five post COVID‐19 Recovery Clinics at the time of referral, with data stored in a fully encrypted Oracle‐based provincial database. The PC‐ICCN has centralized administrative and operational oversight, multi‐stakeholder governance, purpose built data collection supported through clinical operations geographically dispersed across the province, and research operations including data analytics. Results To date, 5364 patients have been referred, with an increasing number and capacity of these clinics, and 2354 people have had at least one clinic visit. Since inception, the PC‐ICCN has received over 30 research proposal requests. This is aligned with the goal of creating infrastructure to support a wide variety of research to improve care and outcomes for patients experiencing long‐term symptoms following COVID‐19 infection. Conclusions The PC‐ICCN is a first‐in‐kind initiative in British Columbia to enhance knowledge and understanding of the sequelae of COVID‐19 infection over time. This provincial initiative serves as a model for other national and international endeavors to enable care as research and research as care.